Kontribusi Dana Zakat, Infak, dan Sedekah terhadap SDGS di Bidang Pangan, Pendidikan, dan Sanitasi: Studi di Pondok Pesantren Al-Maun Bina Akhlaq Mulia Yogyakarta Kreatif Perspektif Ekonomi Islam - Muttaqin, Zainal; Arifah, Cinthiya Zakiah (Program Studi Ekonomi Syariah STAI Senori Tuban, 2025)
This research aims to analyze the management mechanism of zakat, infaq, and alms (ZIS) and its contribution to food security, education, and sanitation at the Al-Maun Bina Akhlaq Mulia Islamic Boarding School. Apart from that, this research also evaluates the socio-economic impact of ZIS management for students and the surrounding community, and examines the potential for replicating this model in other Islamic educational institutions. The method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. The research results show that the ZIS management mechanism in Islamic boarding schools is carried out transparently and participatively by involving various parties, such as partner institutions and the community. ZIS funds play an important role in ensuring the food needs of students, supporting access and quality of education, and improving the sanitation quality of the Islamic boarding school environment. The socio-economic impacts generated include increasing the welfare of students, empowering the community, and strengthening the value of social solidarity. This ZIS management model is considered to have the potential to be replicated by other Islamic educational institutions, provided there is professional management, collaborative support, and innovation in resource management. This research provides a practical contribution to optimizing ZIS funds in strengthening the Islamic boarding school-based education system